2017
DOI: 10.1007/s10935-017-0466-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Health Information Landscape in a Rural, Culturally Diverse Region: Implications for Interventions to Reduce Information Inequality

Abstract: The media is an important source of health information, especially critical in rural communities with geographically-dispersed populations that are harder to reach through other channels. Yet health information is unequally distributed; these information disparities are compounded in rural areas, which may contribute to health disparities. We identify and describe health-related news in a culturally-diverse rural California county characterized by high levels of poverty, unemployment, low educational attainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…Individuals with lower incomes, those with less education, and those of minority race/ethnicity have less access to health information from a variety of sources . These socioeconomic factors characterize many rural areas . Thus, rural residents experience disparities in health information access that may ultimately be contributing to health disparities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals with lower incomes, those with less education, and those of minority race/ethnicity have less access to health information from a variety of sources . These socioeconomic factors characterize many rural areas . Thus, rural residents experience disparities in health information access that may ultimately be contributing to health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…We found that rural residents with limited health literacy had lower access to mass media and scientific literature compared to rural residents with adequate health literacy, but there was no such relationship for urban residents. Compared to urban areas, rural areas have lower levels of media coverage of health information because mass media in rural areas may not have as many resources as urban areas have to conduct in‐depth health reporting or purchase wire stories . Such shortages of health information coverage in rural areas might cause extra challenges for rural residents who have limited health literacy to seek easy‐to‐understand health information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this region is one of the worst air polluted areas in the US [27]. Latino, low-income, and less-educated populations -100 which are overrepresented in the SJV-have less access to health information [28,29]. For 101 minorities that suffer from this lack of access, news media are the primary and trusted sources of 102 health information [30].…”
Section: Introductionmentioning
confidence: 99%